(NkOMPLEKSONY I KOMPLEKSONATY METALLOW (B/s - (NdQTLOWA(B, (NnINA mIHAJLOWNAs; (NtEMKINA(B, (NwERA qKOWLEWNAs; (NpOPOW(B, (NkONSTANTIN iWANOWI^s ((NmOSKWA (B:s (NhIMIQ(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 512-539 (1046 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 539-544s
Keywords: (NkOMPLEKSNYE SOEDINENIQs; (NmETALLYs